Pemberdayaan Pembangkit Listrik Mikro Tenaga Surya dan Sosialisasi Resiko Pencurian Arus PLN di Desa Blang Pulo - Jalil, Saifuddin Muhammad; Sofyan, Diana Khairani; Amri, A; Gani, Subhan A; Syukriah (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2022)
At this time, electricity has become a primary need for the community, the existence of the State Electricity Company (PLN) is very supportive of all community activities. The high use of electricity can cause negative effects for users, where the higher the use of electricity, the greater the costs incurred. This is what triggers the emergence of things that are not wanted in society. One of them is the emergence of a desire to steal electric current. In general, people do not know what the risks are due to stealing the electric current. In addition, there are other ways to reduce excessive use of electricity, one of which is by assembling a solar micro-power plant, of which not many people know about the use of assembling the power plant. Based on this, service is carried out with the aim of providing explanations and adding knowledge to the community in the safe use of electrical energy; provide explanations and increase knowledge for the public about the risk of theft of electrical energy; increase community participation in using and protecting the environment by using alternative energy; foster a strong bond between the Blang Pulo gampong which is the closest village to the Malikussaleh University Bukit Indah campus and the Malikussaleh University academic community, especially the electric energy-saving extension team. The counseling activity on the risk of theft of PLN flows in the village of Blang Pulo is carried out in the following activity methods: Program introduction, assembly and delivery of various forms of energy, especially solar energy; The submission of a frugal living attitude according to Islamic law is accompanied by showing several verses of the Koran and hadith and conveying the risks due to stealing electric current. The expected results of this service are through the micro-solar electricity empowerment program and energy-saving counseling, It is hoped that the awareness, sensitivity and participation of lecturers and the community of Blang Pulo will grow and develop in the safe and efficient use of electrical energy so that there is an adequate supply of electricity and there will be no longer rotating blackouts caused by the limited supply of electricity from the PLN, and explain the consequences if electrical energy is stolen for personal or group use in order to be able to use electrical energy for free.